Induction of reporter genes expression by ionizing radiation and toxins influence on the Drosophila melanogaster genome (Experimental biology, 2020)
In the human environment, there are many factors that can cause genotoxic and mutagenic effects and one of them is ionizing radiation. Radioactive substances like radon, thorium, radium and their decay products during decomposition are able to emit not only highly penetrating gamma radiation, but also form large heavy alpha-particles. Alpha-particles have a low penetrating power, but high ionization energy, about 10 times greater than gamma-rays. Consequently, we researched genotoxic effects of alpha-radiation using a test-system with reporter genes on the Drosophila melanogaster. In nature, the main source of alpha-particles is colorless radioactive gas radon, its isotopes and daughter decay products. It is technically difficult to create sufficiently intense and directed beams of α-radiation on the long-lived radon isotope – 222Rn.  Therefore, for experiments was chosen the 238Pu (Plutonium) isotope, which has the necessary α-line at decay equal to 5.5 MeV. The genotoxic activity of alpha-particles was tested on Drosophila melanogaster with genotype containing genes of luminous proteins. Working of the genetic construction based on the GAL4-UAS system, often used in research to determine gene expression. Genotype also included GADD45 protein gene and GFP gene (green fluorescent protein). This genes combination allows to observe glow of Drosophila organs and tissues after stress factor impact. The sensitivity of construction was checked by chemical mutagen cisplatin, which led to the larvae death at high concentrations, and caused glow of organs at low concentrations. The larvae were exposed to alpha-radiation for 20 hours. Preparations were analyzed on a light microscope with a blue filter and glow of the larval organs was observed. The glow intensity was depending from radiation source. In other words, higher radiation dose caused brighter glow, which correlates with synthesis of luminous protein level. This proves that alpha-radiation from radon and its decay daughter products has a genetic effect.Keywords: alpha radiation, radon, Drosophila, GFP, genotoxicity.